Mean remaining life span: a new clinically relevant parameter to assess the quality of transfused red blood cells. Issue 10 (24th February 2014) - Kuruvilla, Denison J.; Nalbant, Demet; Widness, John A.; Veng‐Pedersen, Peter
Abstract : Background: The quality of transfused red blood cells (RBCs) to treat anemia depends on its potential for oxygen delivery, governed by two properties: 1) initial posttransfusion recovery and 2) life span of initially surviving RBCs. The latter property is poorly evaluated by the traditional mean potential life span (MPL) or mean cell age (MA), because these parameters do not evaluate how long transfused RBCs remain in circulation. Furthermore, evaluation of MPL is based on two problematic assumptions regarding transfused RBCs: 1) they were produced at a constant steady‐state rate and 2) they have similar storage life spans. Study Design and Methods: This work introduces a new parameter, the mean remaining life span (MRL) to quantify transfused RBC survival (TRCS) and presents a simple algorithm for its evaluation. The MRL was calculated for four adult subjects with sickle cell disease and four adult diabetic and nondiabetic subjects using RBC survival data sets with existing TRCS parameters. Results: The RBC survival curves in the sickle cell subjects were nonlinear with rapid decline in survival within the first 5 days. The MRL was approximately 4.6 days. Thus, the MRL was indicative of the survival of all transfused RBCs. For the diabetic and nondiabetic subjects, the RBC disappearance curves did not deviate substantially from a linear decline. Thus, the estimates for MRL ranging from 39 to 51 days are similar to the MA previously computed. Conclusion: MRL overcomes limitations of previously proposed TRCS parameters, is simpler to calculate, and is physiologically and clinically more appropriate.